2017
DOI: 10.1002/2017gl072652
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic metallic iron in lunar soils estimated from the in situ spectra of the Chang'E‐3 mission

Abstract: Submicroscopic metallic iron (SMFe) created by space weathering has strong effects on the optical properties of the lunar surface. Spectra measured in situ by the visible‐near‐infrared spectrometer (VNIS) on board the Chang'E‐3 Yutu rover were used to investigate optical maturity differences at the CE‐3 landing site caused by lander exhaust. SMFe abundances were estimated using Hapke's radiative transfer model. Analysis of the spectrum for a minimally disturbed soil indicates that it contains 0.368 wt % SMFe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…Therefore, the soil in CE‐4 and Apollo 15 landing areas are more mature. The Is/FeO maturity index of the CE‐4 landing site (82 ± 15) is higher than that of the CE‐3 landing site (~53), which indicates that the lunar soil of the CE‐4 landing site is more mature than that of the CE‐3 landing site (Gou et al, 2020; Wang et al, 2017). Agglutinates are the major product of space weathering, the proportion of which in lunar soil increases with the soil maturity.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the soil in CE‐4 and Apollo 15 landing areas are more mature. The Is/FeO maturity index of the CE‐4 landing site (82 ± 15) is higher than that of the CE‐3 landing site (~53), which indicates that the lunar soil of the CE‐4 landing site is more mature than that of the CE‐3 landing site (Gou et al, 2020; Wang et al, 2017). Agglutinates are the major product of space weathering, the proportion of which in lunar soil increases with the soil maturity.…”
Section: Discussionmentioning
confidence: 98%
“…More importantly, the roughness, compactness, maturity, and particle size between the laboratory sample and the actual lunar surface differ by large amounts. The in situ spectra measured by the Visible-Near Infrared Spectrometer (VNIS) on board the China's Chang'E-3 (CE-3) "Yutu" rover revealed that the uppermost surficial regolith is much richer in weathered products, which significantly darken the lunar surface and suppress spectral bands, than the regolith immediately below, and samples returned to Earth could not represent actual lunar surface (Wang et al 2017;Wu & Hapke 2018). Therefore, a spacecraft calibration using the laboratory spectra will have a very large error.…”
Section: Introductionmentioning
confidence: 99%
“…The data including CE-3 VNIR (Visible and Near-infrared Imaging Spectrometer) data and mineral endmembers were used in this study: 1) CE-3 VNIS data Chang'E-3 landed in northern Mare Imbrium at 44.1205º N, 19.5102º W (Wang, Wu et al 2017). Spectra of four locations were measured using the VNIR spectrometer instruments (Fig.1).…”
Section: Datamentioning
confidence: 99%